Defoliation and nitrogen fertilization on the physiological quality of soybean seeds - Cabrera Baptista de Aguiar, Viviane; Alves Fernandes, Marcio; Mario Zuffo, Alan; Felippe Ratke, Rafael; González Aguilera, Jorge; Roque Benetoli da Silva, Tiago; Alves, Charline Zaratin (Revista Ciência Agronômica, 2023)
Stress caused by defoliation can compromise the physiological quality of soybean seeds. However, there is evidence that the application of nitrogen (N) can be an alternative to reduce the qualitative losses in seeds caused by defoliating insects. The objective of this study was to evaluate the effectiveness of topdressing N fertilization in improving the physiological quality of soybean seeds from plants subjected to artificial defoliation. The experimental design was a randomized block arranged in a 2×4 factorial scheme with four replicates. The treatments consisted of two levels of defoliation (33 and 66%) and four doses of N (0, 50, 100, and 150 kg ha-1), using urea (45% N), applied two days after defoliation. Artificial defoliation was performed during the R3 stage by removing one (33%) and two leaflets (66%) from each trifoliate leaf under field conditions. At stage R5.1, leaf area was quantified, and after harvesting, germination, emergence, length, total dry mass, electrical conductivity, total protein content, mass of 1000 seeds, and tetrazolium (vigor and viability) tests were carried out. It was concluded that increasing the defoliation from 33 to 66% impaired the physiological quality of soybean seeds. The use of nitrogen fertilization for coverage after defoliation at the beginning of the reproductive phase cannot minimize qualitative losses in seeds.